Kegiatan Pengabdian Masyarakat Terhadap Deteksi Dini Status Gizi Di Sekolah Dasar Panyaweuyan - Susy Olivia; Farell Christian Gunaidi; Edwin Destra; Nisrina Artanti Prasetiani; Raden Seliwat Agung Aditya; Ranindita Maulya Ismah Amimah; Dianova Soeltanong (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
Nutritional status has a significant impact on the growth and development of children. In Indonesia, the prevalence of nutritional status is as follows: 4% (very thin), 7.2% (thin), 10.8% (overweight), and 8% (obese), as determined by body mass index/age. This can be affected by a variety of variables, including socioeconomic status, personal hygiene, and lifestyle. In the odd semester of 2024, Panyaweuyan Elementary School is populated by 285 students in total. The objective of this service endeavor is to conduct early nutritional status screenings for pupils and girls attending Panyaweuyan Elementary School. By assessing the nutritional status of children through anthropometric measurements such as height, weight, and body mass index, this service activity is developed utilizing the PDCA method. The findings from the assessments indicate that while the majority of pupils enrolled at Panyaweuyan Elementary School possess a healthy nutritional status, a subset remains obese and has a compromised nutritional status. Early detection is critical for preventing and treating nutritional issues in children so that they may develop to their full potential.